Troponin and anti-troponin autoantibody levels in patients with ventricular noncompaction. - Hatice Betül Erer (Public Library of Science (PLoS), 2013)
Ventricular hypertrabeculation/noncompaction is a morphologic and functional anomaly of myocardium characterized by prominent trabeculae accompanied by deep recessus. Dilated cardiomyopathy with left ventricular failure is observed in these patients, while the cause or pathophysiologic nature of this complication is not known. Anti-troponin antibodies are formed against circulating cardiac troponins after an acute coronary event or conditions associated with chronic myocyte necrosis, such as dilated cardiomyopathy. In present study, we aimed to investigate cardiac troponins and anti troponin autoantibodies in ventricular noncompaction/hypertrabeculation patients with/without reduced ejection fraction. A total of 50 patients with ventricular noncompaction and 23 healthy volunteers were included in this study. Noncompaction/hypertrabeculation was diagnosed with two-dimensional echocardiography using appropriate criteria. Depending on ejection fraction, patients were grouped into noncompaction with preserved EF (LVEF >50%, n = 24) and noncompaction with reduced EF (LVEF <35%, n = 26) groups. Troponin I, troponin T, anti-troponin I IgM and anti-troponin T IgM were measured with sandwich immunoassay method using a commercially available kit. Patients with noncompaction had significantly higher troponin I (28.98±9.21 ng/ml in NCNE group and 28.11±10.42 ng/ml in NCLE group), troponin T (22.17±6.97 pg/ml in NCNE group and 22.78±7.76 pg/ml in NCLE group) and antitroponin I IgM (1.92±0.43 µg/ml in NCNE group and 1.79±0.36 µg/ml in NCLE group) levels compared to control group, while antitroponin T IgM and IgG were only elevated in patients with noncompaction and reduced EF (15.81±6.52 µg/ml for IgM and 16.46±6.25 µg/ml for IgG). Elevated cardiac troponins and anti-troponin I autoantibodies were observed in patients with noncompaction preceding the decline in systolic function and could indicate ongoing myocardial damage in these patients.